PENCEGAHAN PENODAAN AGAMA (Kajian atas UU NO.1 TAHUN 1965) - Siti Hanna (UIN K.H. Abdurrahman Wahid Pekalongan, 2010)
Government has right to issue rules that is viewed benefit its citizens in the future. Moreover, it is its main responsibility to guarantee benefit. Indonesia, as a nation that has various citizens from ethnic, tradition, language, religion, and belief, certainly need regulations that are able to maintain harmony relation among them, so that the difference is not a disunion factor. One of them is the issue of the Bill No. 1/PNPS/1965 that can be said as a real proof that Indonesia maintains the harmony of religious life.